High-Resolution Stable Isotope Paleotopography of the John Day Region, Oregon, United States - Kukla, Tyler; Ibarra, Daniel Enrique; Rugenstein, Jeremy K. Caves; Gooley, Jared T.; Mullins, Casey E.; Kramer, Samuel; Moragne, Danielle Y.; Chamberlain, C. Page (Frontiers in Earth Science, 2021)
The John Day region of central Oregon, United States contains ∼50 million years of near-continuous, fossiliferous sedimentation, representing one of the world’s richest archives of Cenozoic terrestrial ecosystems and climate. Stable isotope proxy data from this region are commonly used to infer the elevation history of the Cascades, which intercept westerly moisture in transit to the John Day region. However, the Blue Mountains, which accreted in the Mesozoic, create a region of local high topography that can confound signals of Cascades uplift. John Day deposits, including the John Day Formation, are divided into an eastern facies located within the Blue Mountains and a western facies in the adjacent plains. As a result, the Blue Mountains may have supported gradients in climate and ecology between the eastern and western facies, and constraining these gradients is necessary for reconstructing past topography and ecosystem change. In order to define the Cenozoic extent and magnitude of Blue Mountains topography we use oxygen isotopes in authigenic clay minerals to construct a spatially resolved map of local elevation. We find that the oxygen isotope composition of clay minerals within the Blue Mountains is ∼3‰ lower than in the adjacent high plains, and this offset is mostly constant throughout our record (spanning ∼50 – 5 Ma). We attribute this offset to Blue Mountains topography, either directly from upslope rainout or indirectly through the effect of elevation on local variations in precipitation seasonality. Our results highlight the importance of local topographic features in regional paleotopography reconstructions and provide important biogeographical context for the rich paleo-floral and -faunal records preserved in John Day sediments.